Heavy metal concentrations in fishes from Zakrzówek Reservoir and the Vistula River near Kraków: Human risk assessment - Łuszczek-Trojnar Ewa; Drąg-Kozak Ewa; Szczerbik Paweł; Klaczak Artur; Lelonek Anna; Duda Kinga; Adamska Patrycja (Fisheries & Aquatic Life)
The aim of this study was to compare tissue concentrations of heavy metals (copper (Cu), manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn)) in roach (Rutilus rutilus (L.)), chub (Squalius cephalus (L.)), and bleak (Alburnus alburnus (L.)) from two locations on the Vistula River upstream from Kraków and Zakrzówek Reservoir, a former limestone quarry flooded over 30 years ago that is located close to the center of Kraków. The findings showed that heavy metal concentrations in fishes from the Vistula River upstream from Kraków were higher compared to those in fishes from Zakrzówek Reservoir. The highest heavy metal concentrations were found in hard tissues, such as bone and scales, and the lowest was in muscle tissue. Metal pollution index (MPI), estimated daily intake (EDI), target hazard quotient (THQ), and hazard index (HI) analyses showed no significant non-carcinogenic risk to human health from the consumption of the muscle meat of the fishes analyzed. Cancer risk (CR) values, calculated based on maximum Ni concentrations in fish muscle tissue, did not exceed the upper limit of the acceptable cancer risk range. The findings show that the assessment of heavy metal contamination of fishes should be continued and extended to include other water bodies used for fishing and other xenobiotics that accumulate in fishes and may pose risks to human health.